P256 The practical use of an eHealth platform for inflammatory bowel disease patients: the validation of the IBD Tool web-based tele-monitoring system. (21st January 2022) - Giuffrida, E; Mangia, M; Figini, V; Carli, E; Colombo, A; Mendolaro, M; Lavagna, A; Lia, C; Bonina, M; Martínez De Carnero, F; Morello, E; Cosimato, M; et al.
Abstract: Background: Tele-monitoring and eHealth tools are useful to monitor disease burden and activity in inflammatory bowel disease (IBD). We developed a web-based tele-monitoring platform ( IBD Tool ), in order to monitor granularly disease activity and impact on patients' lives. Aim of this abstract is to report preliminary data on IBD Tool effectiveness. Methods: Consecutive IBD patients were offered the access to the tele-monitoring platform ( IBD Tool ) as a part of an ongoing investigator-initiated observational study, overall 677 patients were enrolled between February and November 2021. Validated questionnaires administered on the platform captured disease activity [Harvey Bradshaw Index (HBI), Simple Clinical Colitis Activity Index (SCCAI), Monitor IBD At Home Questionnaire for Crohn's disease (CD) or for ulcerative colitis (UC): MIAH-CD or MIAH-UC] and disease burden and quality of life. Patients were randomized 1:1 to standard of care (only activity questionnaires required every 3-months) and telemedicine (activity questionnaires required monthly, remaining questionnaires every 3-months). Results: Out of 678 patients enrolled, 585 (87%) are active on the platform and filled overall 14, 297 questionnaires during an average follow-up of 9.8 months, the mean number of questionnaires filled/patient was 24.9. Characteristics of the patient enrolled in the study are presented in Table 1 . Table 1. Characteristics of patients enrolled on the IBD Tool tele-monitoring platform and questionnaires filled Among the 320 cases with 2 or more observations in the IBD Tool platform, it was possible to analyse disease activity variation (summarized as constant, amelioration, or worsening) according to SCCAI or HBI changes ±2 points, results are detailed in Table 2 . Table 2. Charateristics of patients constant, ameliorating or worsening in time. Conclusion: Patients' persistence in the tele-monitoring system is adequate; the systems offer granular and precise multidimensional evaluation of IBD patients.